Transplantace podkovovité ledviny (kazuistika) - Navrátil, P; Veselský, Z; Hafuda, A (Rozhledy v chirurgii, 1997)
The authors submit the case-record of transplantation of a horseshoe, undivided cadaverous kidney from a young donor to an adult man. The authors describe the technical aspect of the operation, discuss possible approaches and provide evidence of the satisfactory function of the graft 18 months after transplantation.
Keywords: transplantace ledvin; mužské pohlaví; ženské pohlaví; Kidney Transplantation; dospělí; Humans; Kidney; Adult; lidé; Female; dítě; ledviny; Male; Child